2021
DOI: 10.12681/healthresj.28191
|View full text |Cite
|
Sign up to set email alerts
|

Clinical indicators as prognostic factors of multi-trauma patients in the Intensive Care Unit

Abstract: Background: In recent years, there has been a growing interest in understanding the role of prognostic factors in patient outcome.Aim: To investigate the role of clinical indicators, and severity-of-disease assessment scales, as prognostic factors in the outcome of multi-trauma patients in the ICU.Material and Method: The sample consisted of 65 ICU multi-trauma patients treated in a hospital in Thessaloniki city, with an average stay of 16.5 days. Clinical indicators such as Glasgow Coma Scale, heart rate, mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 42 publications
(57 reference statements)
1
1
0
Order By: Relevance
“…This finding is parallel with studies conducted in different countries like Qatar [ 27 ], Uganda [ 37 ], Tanzania [ 32 ], Rwanda [ 34 ], Sub-Saharan Africa [ 15 ], Hawassa University Hospital [ 5 ], TASH [ 3 ], and Felegehiwot comprehensive specialized hospital [ 14 ]. The possible reason could be those patients with lower GCS scores are unable to protect their airways and they are at risk of aspiration, have poor infection prevention, are not a candidate for neurosurgery, and have less access to intensive care unit settings [ 40 ]. This research found that neurosurgical interventions are associated with the greatest decrement in the hazard of death among TBI patients.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is parallel with studies conducted in different countries like Qatar [ 27 ], Uganda [ 37 ], Tanzania [ 32 ], Rwanda [ 34 ], Sub-Saharan Africa [ 15 ], Hawassa University Hospital [ 5 ], TASH [ 3 ], and Felegehiwot comprehensive specialized hospital [ 14 ]. The possible reason could be those patients with lower GCS scores are unable to protect their airways and they are at risk of aspiration, have poor infection prevention, are not a candidate for neurosurgery, and have less access to intensive care unit settings [ 40 ]. This research found that neurosurgical interventions are associated with the greatest decrement in the hazard of death among TBI patients.…”
Section: Discussionmentioning
confidence: 99%
“…This was in line with the studies conducted in Ayder Tertiary Hospital, Ethiopia ( 9 ), Kenya ( 28 ), and Turkey ( 29 ). The possible reason could be that those patients with reduced GCS scores are at high risk of aspiration, have compromised ventilator effort, and are at risk of developing intracranial hypertension, which reduces cerebral perfusion and leads to secondary cerebral attacks and death ( 30 ). Maintaining oxygenation and preventing hypercarbia by preventing aspiration, providing supplemental oxygen, and supporting ventilation are critical in managing trauma patients, especially those who have lower GCS scores ( 16 ).…”
Section: Discussionmentioning
confidence: 99%